Construction of a bundle for the safety of patients with mental disorders during hospitalization - Marina Diva de Oliveira; Camila Souza de Almeida; Helen Cristiny Teodoro Couto Ribeiro; Richardson Miranda Machado; Juliano Teixeira Moraes (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to develop a bundle for the safety of psychiatric patients during hospitalization. Methods: a methodological study conducted in two stages. In the first, a comprehensive literature review was developed through a scoping review and conducted to examine evidence on the safety of psychiatric patients during hospitalization. In the second, based on the evidence listed, a set of actions was developed for the safety of psychiatric patients during hospitalization. Results: twenty-six articles published between 2012 and 2022 were used, making it possible to categorize recommendations and build a bundle through four axes: safety culture; clinical decision-making; intervention planning; and interpersonal violence. Conclusions: the scientific evidence provided clear guidance on actions to improve the safety of psychiatric patients during hospitalization. This evidence also highlighted gaps in research, indicating the need for future studies in this area.